2018
DOI: 10.3390/toxins10040131
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Injuries, Ultrastructural Changes, and Depressed TLR Expression in the Small Intestine of Broiler Chickens with Aflatoxin B1

Abstract: To explore AFB1-induced damage of the small intestine, the changes in structure and expression of TLRs (Toll-like Receptors) in the small intestine of chickens were systematically investigated. Ninety healthy neonatal Cobb chickens were randomized into a control group (0 mg/kg AFB1) and an AFB1 group (0.6 mg/kg AFB1). The crypt depth of the small intestine in the AFB1 group was significantly increased in comparison to the control chickens, while the villus height and area were evidently decreased, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…Besides, AFB1 reduced integrity of Caco-2 cells measured using transepithelial electrical resistance assay ( Romero et al, 2016 ). Similarly, intestinal barrier function in broiler was affected by AFB1 ( Wang et al, 2018 ). The adverse effects on the gut from AFB1 exposure include the disruption of intestinal barrier, cell proliferation, cell apoptosis, and immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, AFB1 reduced integrity of Caco-2 cells measured using transepithelial electrical resistance assay ( Romero et al, 2016 ). Similarly, intestinal barrier function in broiler was affected by AFB1 ( Wang et al, 2018 ). The adverse effects on the gut from AFB1 exposure include the disruption of intestinal barrier, cell proliferation, cell apoptosis, and immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of 0.6 mg AFB1/kg diet to broilers for 3 weeks stalled the cell cycle at the G2/M phase causing a reduction in the height jejunum and in the ratio of villus height/crypt, thereby impairing their function as a selective barrier [127]. These findings were recently corroborated by feeding broiler chicken with feed containing 0.6 mg AFB1/kg for up to 21 days and monitoring structural and functional changes in the small intestine [128]. The study showed various structural and histopathological injuries similar to those described above regarding the increased depth of villi with decreased height and area [127], in addition to other histopathological alterations in the small intestine, including mitochondrial vacuolation and loss of cristae, reduced numbers of the absorptive cell goblets and the junctional complexes.…”
Section: Innate Immunitymentioning
confidence: 87%
“…Effects of aflatoxins on immune cells that play key roles in the innate immunity, such as monocytes, macrophages, dendritic cells (DC), and natural killer (NK) cells to restrict their viability, function, or genetic expression of cytokines and chemokines is well documented (Figure 1). Exposure of broilers to AFB1 was reported to repress the transcription of toll-like receptors (TLR) TLR-2, TLR-4, and TLR-7, indicating a suppressive effect on the innate immunity where these receptor proteins are involved in the recognition of external invaders by sentinel cells, e.g., macrophages and dendritic cells, as a key step to trigger this type of immune response [128]. AFB1 at the low dose of 10 ng/mL was also reported to reduce the antigen-presenting activity of porcine dendritic cells, although this reduction could not be associated with down-regulation of the expression of TLRs or specific cytokines [134].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Mycotoxins elicit similar toxic effects among humans and animals. In bird intestines, various methods have been used to study the effects of toxins [ 46 , 47 ]. Some data revealed the immuno- and cytotoxic effect of ochratoxin A on intestinal epithelium and MALT-system (mucosa-associated lymphoid tissue), modifying the intestinal barrier and thus increasing receptiveness to different associated diseases [ 41 ].…”
Section: Discussionmentioning
confidence: 99%